Sustainable Palm Oil Certification for Sustainable Food: Are Indonesian Consumers Buying? - Amalia, Bunga Alfausta; Meyrizka Utami, Alivia (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2025)
Consumers are increasingly hesitant to engage in widespread greenwashing practices in palm oil products. The Roundtable on Sustainable Palm Oil (RSPO) exists as an international standard aimed at encouraging consumer consumption towards more sustainable palm oil. This study uses the Cognitive–Affective–Behavioral (CAB) framework to analyze factors influencing green purchasing behavior for RSPO-labeled food products in Indonesia. The cognitive dimension is represented by green brand image and green brand loyalty, while the affective dimension is represented by green brand love. This is a quantitative study using a survey method. A total of 303 respondents were collected through a purposive sampling technique with the criteria of knowing the RSPO certification and label and having purchased RSPO-labeled food products in the past three months. Data analysis was conducted using SmartPLS 4.0. The results show that green brand image and green brand loyalty have a positive and significant effect on green purchasing behavior, while green brand love has no significant effect. This suggests that the emergence of emotions towards a brand does not automatically encourage consumers to purchase environmentally friendly products. Future research can use a qualitative approach with in-depth interviews or focus group discussions to understand the reasons behind this phenomenon. The study also recommends other variables such as consumer knowledge about sustainability or risk perception towards sustainable products.